Consumer response to retail performance of organic food retailers. Issue 2 (2014) - ,; ,
Abstract : Purpose – Understanding how retail performance can reduce risk perceptions and influence behavioral intentions remains a key issue for researchers. Consumer evaluations of a retailer's performance may form their risk perceptions and positive behavioral intentions toward the retailer. This study aims to extend previous research by proposing an integrative model that examines how three retail performance dimensions (product quality, service quality, and price fairness) influence consumer trust, risk perceptions, and repatronage intentions in the context of organic food retailing.Design/methodology/approach – Empirical data were collected from face‐to‐face interviews guided by a structural questionnaire. Consumers of organic food retailers located in Taiwan were asked to participate in the research and 416 usable questionnaires were collected. Structural equation modeling (SEM) through LISREL 8.70 was used to analyze the data.Findings – Results show that both product quality and price fairness have direct effects on consumer trust, risk perceptions, and indirect effects (through trust in retailer and transaction risk perceptions) on the intent to revisit an organic food retailer. Service quality only affects consumer trust directly, but not perceived transaction risk. In addition, service quality does not have a significant indirect effect on revisit intention.Originality/value – This study is the first to research essential issues for understanding the role of retail performance dimensions on transaction risk perceptions in organic food marketing practices in Taiwan.